Perbandingan Efektifitas Metilprednisolon Intravena dengan Oral pada Kasus Grave Ophthalmopathy di RSUP Dr M Djamil Padang - Efendi, Mardijas; Hendriati, Hendriati; Primasakti, Pattih; Erwen, Yolanda Wulandari (Jurnal Kesehatan Andalas, 2025)
Grave's Ophthalmopathy can occur in three phases depending on the inflammatory process.  Immunosuppressant therapy is an anti-inflammatory option for managing the active phase of GO.  A study showed a significant improvement in GO proptosis in patients treated with methylprednisolone.  Objective: To determined the frequency of proptosis in Thyroid Eye Disease  (TED) patients and the differential effect of oral or intravenous steroid administration.  Methods: This study was a prospective cohort study through medical record data from March 2023 to March 2024.  The subjects are all inpatients with thyroid eye disease in Dr M Djamil General Hospital, Padang.  T-tests were performed to determine each group's different perceptions.  Results: Thirty-six subjects with Grave’s ophthalmopathy.  The effect size of the changes in Hertel values in patients given both oral and intravenous corticosteroid therapy is significant in both eyes.  The effect size of the oral therapy is significant, with 0.341 in the right eyes and 0.303 in the left eyes.  The intravenous therapy is also significant, with the effect size 0.347 in the right and 0.271 in the left.  The change of Hertel value in patients given both oral and intravenous corticosteroid therapy is significant in the right eyes (p = 0.009 and p = 0.008).  Conclusion: Oral and injectable corticosteroids have similar effectiveness, thus providing flexibility in therapy selection for patients with thyroid eye disease. Keywords:  Grave ophthalmopathy, intravenous methylprednisolone, oral methylprednisolone